Analisis Faktor-Faktor Keamanan Yang Mempengaruhi Dompet Digital di JABODETABEK - Safitry, Julia; Trihandoyo, Agus (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Since 2014 Bank Indonesia has publicized the National Non-Cash Movement (GNNT), with the aim of building a safe, effective and smooth payment system so that the country’s financial system can function successfully and efficiently. Digital payment systems in Indonesia are quite diverse, one of which is a digital wallet. However, the increasing use of digital wallets has also potential digital security threats that need to be monitored. This study aims to determine what security factors influence users in using digital wallets for users in JABODETABEK area. By using a descriptive quantitative approach, the object of this research is the population of JABODETABEK area who has transacted using digital wallets. Purposive random sampling technique has been used. Data collection was done though questionnaires in the form of Google Forms, and distributed via Instagram, Twitter and Whatsapp. This study uses data analysis techniques for classical assumption tests, multiple linear regression and hypothesis testing, and uses SPSS 25 tools for data analysis. The results of the analysis show that the combination of variables, such as transaction speed, authentication, encryption mechanism, software capabilities, protection of personal details and information provided influence the usage of digital wallets, with an influence factor of 31,1%. Furthermore, authentication, software capabilities, protection of personal details and information provided variables influence individually the usage of digital wallets.